Working Capital Management: A Study on British American Tobacco Bangladesh Company Ltd. - Sayaduzzaman, Md. (Journal of Nepalese Business Studies, 2007)
The efficiency of working capital management of British American Tobacco Bangladesh Company Ltd. is highly satisfactory due to the positive cash in flows, planned approach in managing the major elements of working capital. Applications of multi-dimensional models of current assets mix may have positive impact on the continuous growth & development of this multinational enterprise. This depends on co-operation of the stakeholders and business environment in the contest of globalization. Journal of Nepalese Business Studies 2006/III/1 pp. 78-84